Experimental Infection of River Catfish Mystus Nemurus with Vibrio Parahaemolyticus and Molecular Characterization of the Isolates - Musa, Najiah (2002)
Declining marine fish resources in Malaysia have led to the innovation of rearing indigenous freshwater river catfish Mystus nemurus, locally known as 'baung' in brackishwater. This however will inevitably expose the fish to the pathogen, Vibrio parahaemolyticus that is ubiquitous in brackishwater. The present research was undertaken to study the virulence and pathogenicity of clinical and environmental V. parahaemolyticus isolates in M. nemurus. Vibrio parahaemolyticus isolates from various sources and locations in Peninsular Malaysia were identified based on morphological, biochemical and physiological characteristics. Virulence studies revealed that clinical V. parahaemolyticus from clinical cases were more virulent (p< 0.05) to M nemurus as compared to environmental isolates. The virulence was categorized as virulent, moderately virulent, weakly virulent and avirulent. The most virulent isolate (Fl) was used to infect fish via intraperitoneal (IP), intramuscular (IM) and immersion routes. The LD50 results revealed that IP exposure was most pathogenic, following by IM and immersion exposures. Intraperitoneal exposure caused toxemia in fish while 1M exposure caused localized lesions at the injection sites, and immersion exposure caused only mild inflammatory responses on the gills and the scraped skin. Random amplification polymorphic DNA (RAPD) revealed DNA polymorphism in all isolates tested, indicative of high variability among the V parahaemolyticus isolates. Dendrogram revealed a distant genetic relationship between the virulent (Fl) and avirulent (W4) isolates. Antibiogram showed resistance to intennediate to erythromycin, and 90% of the isolates were intennediate to cephalosporins and cefotaxim. The absence of plasmids in all isolates indicated that antimicrobial resistance of the isolates were chromosomally mediated. Partial sequence analysis of the toxR and toxS genes of isolates Fl and W4 revealed a very high homology (97%). The genetic variations of toxR fragment resulted in 59 to 77% amino acid homology. This might have contributed to the different degrees of virulence of the isolates. The toxS fragment showed lOO% amino acid homology, indicating that this fragment was more conserved than toxR gene fragment. It appeared that not all V. parahaemolyticus isolates could induce infection in M nemurus. However, slight genetic variations in toxR gene fragment of V parahaemolyticus isolates could contribute to different degree of virulence. Mystus nemurus was least susceptible to the immersion challenge of a virulent V. parahaemolyticus isolate.